1967
DOI: 10.1177/002188636700300407
|View full text |Cite
|
Sign up to set email alerts
|

Confrontation as a Training Design in Complex Organizations: Attitudinal Changes in a Diversified Population of Managers

Abstract: The "confrontation technique" has been used successfully in training designs in complex organizations, and this study at once reinforces and extends existing experience. Specifically, what follows is a report on an application of the technique that induced favorable attitudinal changes in the marketing area of a large firm. The similarities of this study with existing ones encompass both design and results. Basically, the design required the exchange of "images" between individuals or organization units. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Golembiewski and Blumberg (1967) attested to the efficacy of training in the 'critical core skills' and the use of the stated procedures as reported in their study, an improvement in the commitment of trainees to decisions and attitude towards co-operation as well as empathy in pre-and post-tests. Arak (1990), Burrel and Vogis-Turf (1990) and Davis (1986) found that 95-98% of conflicts mediated by trainees in the 'critical core skills' of the co-creative process of conflict resolution had lasting and stable agreements because the parties were committed to the decisions made.…”
Section: Theoretical Considerationmentioning
confidence: 77%
See 1 more Smart Citation
“…Golembiewski and Blumberg (1967) attested to the efficacy of training in the 'critical core skills' and the use of the stated procedures as reported in their study, an improvement in the commitment of trainees to decisions and attitude towards co-operation as well as empathy in pre-and post-tests. Arak (1990), Burrel and Vogis-Turf (1990) and Davis (1986) found that 95-98% of conflicts mediated by trainees in the 'critical core skills' of the co-creative process of conflict resolution had lasting and stable agreements because the parties were committed to the decisions made.…”
Section: Theoretical Considerationmentioning
confidence: 77%
“…Critical core skills of co-creative conflict resolution Golembiewski and Blumberg (1967) and Arak (1990) observed that trainees are successful in co-creative conflict resolution process if they are primarily trained Downloaded by [University of California Santa Cruz] at 01:47 27 November 2014 to become sensitive and willing to change certain aspects of their behaviour and exhibit qualities termed 'critical core skills' during social relationship. Clements et al (2000) listed the aspects of behaviour as: ability of trainees to trust opponents during interaction; maintenance of integrity during conflict resolution process; forgiveness of opponents; co-operation with opponents to resolve issues; empathy; taking responsibility for one's actions; and commitment to the decisions made in the resolution of conflicts.…”
Section: Theoretical Considerationmentioning
confidence: 99%
“…These perceptions are shared, and the problems they indicate are confronted and resolved. The design, or a variation thereof, has been utilized in dealing with intergroup conflict (Argyris, 1967;Blake, Shepard, & Mouton, 1954;Golembiewski & Blumberg, 1969) and interpersonal and intragroup conflict (Beckhard, 1969;Bennis, 1969;Boss, 1975;Boss, Gouws, & Nagai, 1978;Golembiewski & Blumberg, 1967;Golembiewski & Kiepper, 1976). Two important factors contributed to the adoption of the 3-D-image design.…”
Section: Designmentioning
confidence: 99%
“…Since then approaches developed through the NTL Institute for Applied Behavioral Science have been tried out in countless organizations. Although the T-group has been associated with the National Training Laboratories (NTL) and the laboratory method in general (Bradford, Gibb, and Benne, 1964) and is still practiced as the pivotal tool in many organizational change programs (Bennis, 1966;Schein and Bennis, 1965;Argyris, 1964;Rice, 1965), other approaches have been effective (Schein and Bennis, 1965;Crosby and Schmuck, 1969;Golembiewski and Blumberg, 1967). The present paper describes procedures, exercises, methods, sequences, and data we have used in organizational training with schools and school districts.'…”
mentioning
confidence: 99%